2010
DOI: 10.1007/s10569-010-9261-y
|View full text |Cite
|
Sign up to set email alerts
|

Where are the Uranus Trojans?

Abstract: The area of stable motion for fictitious Trojan asteroids around Uranus' equilateral equilibrium points is investigated with respect to the inclination of the asteroid's orbit to determine the size of the regions and their shape. For this task we used the results of extensive numerical integrations of orbits for a grid of initial conditions around the points L4 and L5, and analyzed the stability of the individual orbits. Our basic dynamical model was the Outer Solar System (Jupiter, Saturn, Uranus and Neptune)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…For Uranus a similar study by Dvorak, Bazsó & Zhou (2010) concluded that Trojans on low inclination orbits could survive over timescales of 10 9 ⋆ Corresponding author: e-mail: akos.bazso@univie.ac.at years. Both studies used as dynamical model the outer Solar system including all four gas planets, thus accounting for mutual perturbations of the planets; but a more complex model can also obscure the fundamental features of Trojan motion.…”
Section: Solar Systemmentioning
confidence: 97%
“…For Uranus a similar study by Dvorak, Bazsó & Zhou (2010) concluded that Trojans on low inclination orbits could survive over timescales of 10 9 ⋆ Corresponding author: e-mail: akos.bazso@univie.ac.at years. Both studies used as dynamical model the outer Solar system including all four gas planets, thus accounting for mutual perturbations of the planets; but a more complex model can also obscure the fundamental features of Trojan motion.…”
Section: Solar Systemmentioning
confidence: 97%
“…The most important are the low order resonances. Recent studies indicate the ever increasing interest in resonances in the Solar System (Pástor et al 2009;Cachucho et al 2010;Dvorak et al 2010) and in exoplanetary systems (Gayon et al 2009;Schwarz et al 2009;Hadjidemetriou et al 2009;Voyatzis 2010, 2011;Libert and Tsiganis 2011). However, higher order resonances can also become important, especially at high eccentricities.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that, contrary to this view and in spite of the destabilizing role of Saturn, Uranus still can actively capture temporary co-orbitals. Regarding the question of stability, (83982) Crantor's orbital inclination is close to the edge of one of the stability islands in i identified by Dvorak et al (2010), but 2010 EU 65 moves outside the stability islands proposed in that study, yet it seems to be more stable than (83982) Crantor. This comparatively better stability strongly suggests that not only inclination but also eccentricity play an important role in the longterm dynamics of these objects.…”
Section: Discussionmentioning
confidence: 56%
“…However, Uranus appears not to be able to efficiently capture objects into the 1:1 commensurability today even for short periods of time (Horner & Evans 2006). The stability of hypothetical Uranus co-orbitals, specifically those moving in tadpole orbits, has been studied by Dvorak et al (2010), who have found that the orbital A&A 551, A114 (2013) inclination is the key parameter regarding stability, only the inclination intervals (0, 7) • , (9, 13) • , (31, 36) • and (38, 50) • appear to be stable. This scarcity of Uranus co-orbitals seems to be confirmed by current observational results.…”
Section: Introductionmentioning
confidence: 99%